La cripta funeraria de los marqueses de Astorga - Morais Vallejo, Emilio (Estudios humanísticos. Geografía, historia y arte, 1998)
In 1610 the marquis of Astorga, Pedro Alvarez Osorio, entrusted to the architect Pedro Alvarez de la Torre with the building of a funeral crypt under the presbitery of the cathedral of Astorga. This chapel was built following the principies of styles embodied in the 17th century classicism architecture.